MoSi2-based cylindrical susceptor for rapid high-temperature induction heating in air. Issue 15 (15th October 2020) - Kim, Yo Han; Shin, Tae Ho; Myung, Jae-ha
Abstract: Conductive susceptors are necessary for heating non-conductive materials in induction heating systems. Susceptor materials should have sufficient electrical conductivity and thermal/chemical stability under a range of environmental conditions. However, many susceptor materials oxidize in high-temperature environments, resulting in degradation and poor durability. Here, we used intermetallic MoSi2 ceramics as a susceptor material and designed a cylindrical susceptor to apply to rapid high-temperature induction heating in an oxidizing environment. MoSi2 was prepared by self-propagating high-temperature synthesis (SHS), and then used to fabricate cylindrical susceptors by slip casting. The optimal thickness of the susceptor was controlled by modelling. A MoSi2 -based cylindrical susceptor with SiO2 protective layer showed higher heating rate (4.2–26.8 °C/s at 0.5–2.5 kW) than a commercial rod-type susceptor (7.7–13.6 °C/s at 1.0–2.5 kW) of the same material. In addition, our susceptor endured high temperatures below 1700 °C and severe thermal cycle (700–1600 °C, heating for 2min and cooling for 1min) during 36 cycles. In general, these results demonstrate that the MoSi2 -based susceptor can be applied to a rapid induction heating furnace that can be used in air at a high temperature of 1600 °C (equal to the available temperature of a commercial graphite susceptor in H2 ).